Analisis Faktor Keterlekatan Kerja terhadap Kesiapan Penerapan Rekam Medis Elektronik di Rumah Sakit Pertamina Bintang Amin - Gewang, Annissa Achmadsyah; Farich, Achmad; F, Christin Angelina; Sudirahayu, Ika; Riyanti, Riyanti (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The implementation of Electronic Medical Records (EMR) in hospitals is an essential element in Indonesia's healthcare strategy aimed at enhancing the efficiency and accuracy of healthcare services. With the deadline set by the Ministry of Health of the Republic of Indonesia, evaluating readiness and determinant factors becomes a necessity. Therefore, this research focuses on analyzing the factors of work engagement towards the readiness for implementing electronic medical records at Pertamina Bintang Amin Hospital in 2023. Research method used is quantitative with a cross-sectional design. A sample of 157 respondents, who are healthcare workers responsible for implementing EMR, was selected using proportional random sampling techniques. The dependent variable assessed is the readiness for EMR implementation, and the independent variables include work engagement dimensions: emotional engagement, intellectual engagement, physical engagement, and spiritual engagement. Research results showed that the independent variables related to EMR implementation readiness are emotional engagement (p-value 0,003), intellectual engagement (p-value 0,012), and physical engagement (p-value 0,011). The most dominant influencing factor is emotional engagement. These findings are expected to serve as a reference for the hospital to enhance employee work engagement, thus preparing them for EMR implementation effectively. Emphasis should be placed on a deep understanding of the electronic system, its benefits, and the necessary psychological support, so that staff can be more prepared and confident in using the new technology. This will help minimize obstacles and improve the efficiency of EMR implementation in the hospital. Keywords: Electronic Medical Record Implementation Readiness, Work Engagement, Hospital  ABSTRAK Penerapan Rekam Medis Elektronik (RME) di rumah sakit adalah elemen penting dalam strategi kesehatan Indonesia yang bertujuan untuk meningkatkan efisiensi dan akurasi layanan kesehatan. Dengan tenggat waktu yang telah ditetapkan oleh Kementerian Kesehatan Republik Indonesia, evaluasi kesiapan dan faktor-faktor determinan menjadi suatu keharusan. Oleh karena itu, penelitian ini memfokuskan pada analisis faktor keterlekatan kerja terhadap kesiapan penerapan rekam medis elektronik di Rumah Sakit Pertamina Bintang Amin Tahun 2024. Metode penelitian yang digunakan berupa kuantitatif dengan rancangan cross sectional. Sampel yang diambil sebanyak 157 responden yang merupakan petugas kesehatan yang akan mengimplementasikan RME dengan teknik proportional random sampling. Variabel dependen yang dinilai yaitu kesiapan penerapan RME dan variabel independen berupa keterlekatan kerja; keterlekatan emosional, keterlekatan intelektual, keterlekatan fisik, dan keterlekatan spiritual. Hasil penelitian didapatkan variabel independen yang berhubungan dengan kesiapan penerapan RME adalah faktor keterlekatan emosional (p-value 0,003), keterlekatan intelektual (p-value 0,012), dan keterlekatan fisik (p-value 0,011). faktor paling dominan yang berpengaruh berupa keterlekatan emosional. Hasil ini diharapkan dapat menjadi acuan bagi rumah sakit tersebut dalam meningkatkan keterlekatan kerja petugas agar siap dalam penerapan RME di rumah sakit. Fokus diberikan pada pemahaman mendalam tentang sistem elektronik, manfaatnya, serta dukungan psikologis yang diperlukan agar para petugas dapat lebih siap dan percaya diri dalam menggunakan teknologi baru tersebut sehingga meminimalkan hambatan dan meningkatkan efisiensi penerapan RME di rumah sakit. Kata Kunci: Kesiapan Penerapan Rekam Medis Elektronik, Keterlekatan Kerja, Rumah Sakit